EFFECTS OF HEARING IMPAIRMENT ON SOCIAL ABILITIES IN THE ELDERLY - Sabri, Tsabita Salsabila; Akib, Marlyanti Nur Rahmah; Pratama, Ahmad Ardhani; Wahyu, Sri; Zainal, Muh. Reza (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2025)
Hearing loss is a global health problem with increasing prevalence, especially in the elderly. This condition not only affects communication skills, but also affects the social and psychological aspects of individuals, such as social isolation, depression, and decreased self-confidence. Difficulties in interacting can lead to limitations in social participation and self-adjustment, which ultimately reduces the quality of life of the elderly. This study aims to determine the characteristics of individuals who experience hearing loss in the elderly, determine the effect of hearing loss on social disabilities in the elderly, determine the social disabilities that occur as a result of hearing loss in the elderly. This research uses quantitative methods with an analytical survey approach and cross-sectional design. The results showed that of the 40 respondents, the majority were in the age range of 45-59 years. A total of 25 respondents (62.5%) were female, and 15 respondents (37.5%) were male. Of these, 29 respondents (72.5%) had hearing loss, while 11 respondents (27.5%) did not have a loss. Statistical analysis showed that hearing loss had a significant effect on social disability in the elderly (p-value = 0.001), Most experienced mild social disability as many as 26 respondents (22.5%). Hearing loss causes difficulties in communication, which can increase the risk of social isolation and reduce their quality of life.